The structure of wages during the economic transition in Romania - Skoufias, Emmanuel (International Food Policy Research Institute, 1999)
This paper uses cross-sectional individual data from the 1994 Integrated Household Survey of Romania to analyze the determinants of male and female wages in public and private enterprises. Using quantile regression, the rate of return to education and experience at different quantiles of the wage distribution is estimated. Higher levels of education are significantly associated with higher wages for both males and females in public firms. In private firms, only college education is correlated with significantly higher wages. Differences in individual characteristics are found to explain the highest portion of the male-female wage differential in Romania in both sectors.